EVALUASI PERTUMBUHAN IKAN LELE DUMBO (Clarias gariepinus) PADA BUDIDAYA AKUAPONIK DENGAN SAYURAN SAWI (Brassica rapa var. parachinensis) - Marlyn Kallau; Theresia Ginting; Yusuf Kamlasi (Partner, 2016)
Aquaponic refers to any system that combines conventional aquaculture with hydroponics in a symbiotic environment. In this study, catfish was cultured with green cabbage. The aim of this study was to observe catfish growth in aquaponics system. The growth parameters measured included feed consumption (g/day/fish), growth (g), growth rate (%/day), mean metabolic body weight (kg0.8), metabolic feed intake (g/ kg0.8/day), relative growth rate per metabolic weight (g/kg0.8/day), relative feeding rate (%BW/day), relative feeding rate per metabolic weight (g/kg0.8) and feed conversion. Factorial randomized trial was used with two factors namely fish stocking density (P) and plant substrate composition (S) with three replications. Stocking density factor consisted of two treatments which were 75-125 individuals per m2 (P1) and 126-175 individuals per m2 (P2). The composition of the substrate included two treatments, namely S1 (70% gravel+30% palm fibres) and S2 (70% pumice+30% palm fibres). The data shown that there is no significant difference of substrate and interaction (stocking density x substrate) factors to the growth of catfish (P>0.05). Whereas, for the treatment of stocking densities, a significant difference (P <0.05) was found on four growth parameters (initial weight, SGR, RGRm and feed consumption).Keywords : aquaponics, catfish, green cabbage and fish growth